The impact of problematic mobile phone use and the number of close friends on depression and anxiety symptoms among college students - Wang, Wei; Xu, Huiqiong; Li, Shuqin; Jiang, Zhicheng; Sun, Yanjun; Wan, Yuhui (Frontiers in Psychiatry, 2024)
Background: Psychological problems often occur in college students, with the most common ones being depression and anxiety symptoms. Exploring the risk factors that influence depression and anxiety symptoms in college students is essential to promote their physical and mental health.Objective: This study aimed to investigate the independent and interaction effects of problematic mobile phone use (PMPU) and the number of close friends (NCFs) on depression and anxiety symptoms and the comorbidity of these symptoms among college students.A cross-sectional survey was conducted in Huainan, Anhui Province, and Suzhou, Jiangsu Province in China from October to December 2022. Data from 7,617 college students were collected. The Patient Health Questionnaire and Generalized Anxiety Disorder-7 were used to evaluate depression and anxiety symptoms. The PMPU data were collected by the Mobile Phone Addiction Type Scale. Multinomial logistic regression models were performed to examine the associations of PMPU and NCFs with depression and anxiety symptoms and their interaction effects.Results: PMPU and lack of close friends significantly increased the risk of depression and anxiety symptoms and the comorbidity of these symptoms in college students (P < 0.001). In addition, the effects of PMPU and lack of close friends on depression and anxiety symptoms in college students were interactive (P < 0.001). No significant sex differences were found.Conclusions: PMPU and lack of close friends are important risk factors for depression, anxiety, and the comorbidity of these symptoms in college students in China.